Higher mobility of freshwater mussels in response to unsuitable habitat conditions - Andreas H. Dobler; Astrid N. Schwalb; Juergen Geist (PLoS ONE, 2026)
Movement behavior of freshwater invertebrates is largely understudied, although gaining insights into behavioral responses may be crucial to better understand their ecology and to guide their conservation. The objective of this study was to examine whether movement distances and burrowing depths of Unio nanus , a species of the U. crassus complex, and Anodonta spp. would vary between three different habitats (dominated by either U. nanus or Anodonta spp. or in which both species were rare) in a headwater stream in southern Germany within longer (8 weeks) and shorter (48 hours, controlled for substrate) field experiments. We hypothesized that mussels should be the most mobile (i.e., larger locomotion distances) and burrow less in presumably unsuitable habitats where they are rare. Both taxa were most mobile at a sidearm location where both species were rare, and which had the lowest water depth and flow velocity. While U. nanus burrowed significantly deeper at the other faster-flowing sites, burrowing of Anodonta spp. was more variable and did not significantly differ between sites. The results suggest that low water levels may trigger increased mobility in both species, potentially as an adaptation to avoid drying. The stronger behavioral response of U. nanus may reflect its adaptation to more dynamic, lotic environments.